Karrikin Improves Osmotic and Salt Stress Tolerance via the Regulation of the Redox Homeostasis in the Oil Plant Sapium sebiferum - Shah, Faheem Afzal; Wei, Xiao; Wang, Qiaojian; Liu, Wenbo; Wang, Dongdong; Yao, Yuanyuan; Hu, Hao; Chen, Xue; Huang, Shengwei; Hou, Jinyan; Lu, Ruiju; Liu, Chenghong; et al. (Frontiers in Plant Science, 2020)
Karrikins are reported to stimulate seed germination, regulate seedling growth, and increase the seedling vigor in abiotic-stress conditions in plants. Nevertheless, how karrikins alleviate abiotic stress, remains largely elusive. In this study, we found that karrikin (KAR1) could significantly alleviate both drought and salt stress in the important oil plant Sapium sebiferum. KAR1 supplementation in growth medium at nanomolar (nM) concentration was enough to recover seed germination under salt and osmotic stress conditions. One nM KAR1 improved seedlings biomass, increased taproot length, and lateral roots number under abiotic stresses, suggesting that KAR1 is a potent alleviator of abiotic stresses in plants. Under abiotic stresses, KAR1-treated seedlings had higher activity of the key antioxidative enzymes, such as superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase, in comparison with control, which leads to the lower level of hydrogen peroxide, malondialdehyde, and electrolyte leakage. Moreover, the metabolome analysis showed that KAR1 treatment significantly increased the level of organic acids and amino acids, which played important roles in redox homeostasis under stresses, suggesting that karrikins might alleviate abiotic stresses via the regulation of redox homeostasis. Under abiotic stresses, karrikins applications did not increase the endogenous absicic acid level, but altered the expression of several ABA signaling genes, such as SNF1-RELATED PROTEIN KINASE2.3, SNF1-RELATED PROTEIN KINASE2.6, ABI3, and ABI5, suggesting potential interactions between karrikins and ABA signaling in the stress responses. Conclusively, we not only provided the physiological and molecular evidence to clarify the mechanism of karrikins in the regulation of stress adaptation in S. sebiferum but also showed the potential value of karrikins in the agricultural practices which will lay a foundation for further studies about the role of karrikins in the abiotic stress alleviation in plants.